Assessment of Underground Water Contamination and Effect of Textile Effluents on Noyyal River Basin In and Around Tiruppur Town, Tamilnadu - A. Geetha; P. N. Palanisamy; P. Sivakumar; P. Ganesh Kumar; M. Sujatha (E-Journal of Chemistry)
A systematic study has been carried out to assess the underground water contamination and the effect of textile effluents on Noyyal River basin in and around Tiruppur Town. Twenty six sampling locations were selected at random and the ground water samples were collected mostly from tube wells at Noyyal River basin in and around Tiruppur area. The samples were analyzed for major physical and chemical water quality parameters like pH, alkalinity, electrical conductivity (EC), total dissolved solids (TDS), total hardness (TH), Ca, Mg, Na, K, Cl & SO42-. It was found that the underground water quality was contaminated at few sampling sites due to the industrial discharge of the effluents on to the river or land from the Tiruppur town. The sampling sites namely Orathupalayam, Karuvapalayam, Kulathupalayam, Uttukuli and Kodumanalpudur showed high deviations in total alkalinity, total hardness, Ca, Mg and chloride concentrations. Hence our study concludes that the underground water quality study in this region shows a constant variation in different parameters in different periods (before and after monsoon). So it is highly important to take periodical monitoring of the underground water quality in this region for our future sustainability